Crystal structure and Hirshfeld surface analysis of a zinc xanthate complex containing the 2,2′-bipyridine ligand - Qadir, Adnan M. (Acta Crystallogr E Crystallogr Commun, 2019)
In the title compound, (2,2′-bipyridine-κ(2) N,N′)bis(2-methoxyethyl xanthato-κS)zinc(II), [Zn(C(4)H(7)O(2)S(2))(2)(C(10)H(8)N(2))], the Zn(II) ion is coordinated to two N atoms of the 2,2′-bipyridine ligand and two S atoms from two 2-methoxyethyl xanthate ligands. The Zn(II) ion lies on a crystallographic twofold rotation axis and has distorted tetrahedral coordination geometry. In the crystal, molecules are linked by weak C—H⋯O hydrogen bonds, forming supramolecular chains propagating along the a-axis direction. Weak intramolecular C—H⋯S hydrogen bonds are also observed. The intermolecular contacts in the crystal were further analysed using Hirshfield surface analysis, which indicates that the most significant contacts are H⋯H (36.3%), followed by S⋯H/H⋯S (24.7%), C⋯H/H⋯C (15.1%), O⋯H/H⋯O (14.4%), N⋯H/H⋯N (4.1%) and C⋯C (2.9%).